STATUS HUKUM KARYAWAN TETAP TANPA PERPANJANGAN PKWT DALAM PP NOMOR 35/2021 - Wiratama, Adit (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Fixed-Term Employment Agreement (PKWT) is the basis of an employment relationship based on a certain period of time. However, in practice, workers often continue to work even though the PKWT period ends without a written extension. This case occurred in the Aviation Security Department of PT. Angkasa Pura Solusi, Soekarno Hatta Airport. This study aims to determine how the implementation of the PKWT between employees and PT. Angkasa Pura Solusi and to determine the legal status of employees who do not extend the PKWT but still work based on PP 35/2021. This study uses a normative legal method to examine the implementation of PKWT and the legal status of employees who continue to work without an extension. The results show that the implementation of PKWT is generally in accordance with PP Number 35 of 2021, but there are still discrepancies in the field. Employees who continue to work without a written extension are considered to have changed status to permanent workers (PKWTT) according to Article 11 of PP 35/2021. This emphasizes the importance of administrative compliance to prevent industrial relations disputes.Keywords: Employee Legal Status, Without Extension, PKWT, PP 35/2021.